(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The concept of power is one of the concepts inherent to man at all political, social, and material levels. From this point of view, its connotations and symbolism have varied since ancient times until now, but Foucault, the focus of our research, was the most profound in his interpretation of the meaning of power, as he demolished the common meaning of it as it is linked to the state and the law to establish its new meaning as a practice and a strong relationship.